Correlates of mothers’ nutritional status in developing economies: evidence from demographic and health surveys - Mariam Abbas Soharwardi; Tusawar Iftikhar Ahmad; Mussab Ali Khan Manj; Rana Ejaz Ali Khan (Journal of the Pakistan Medical Association, 2021)
Objective: The paper investigates the determinants of nutritional status of mothers in developing countries. Method: For a panel of 38 developing countries, data were obtained from the nationally representative Demographic Health Surveys (DHS). Married women of reproductive ages (15 to 45 years), currently living with their husbands were selected as the target population. Body mass index was used as a proxy measure to gauge nutritional status. Both bivariate and multivariate statistical analyses were employed to assess the socioeconomic determinants of mothers’ nutritional status. Results: As compared to the reference category, the probability of being malnourished was: the lowest (OR=0.397, 95% CI=.0341-0.462) among the mothers with higher education, the highest (OR=1.112, 95% CI=1.043-1.186) among the mothers who belonged to the age category 15-19 years at their first birth, the lowest (OR=0.309, 95% CI=0.280-0.341) among the mothers with higher women empowerment status, high (OR=1.003, 95% CI=.848-1.18) among the women having one year birth interval, higher (OR=1.724, 95% CI=1.669-1.186) among the women who take no antenatal visit during pregnancy, higher(OR=1.795, 95% CI=1.757-1.836) among the mothers having total number of children ever born more than four, relatively higher (OR =0.846, 95% CI=0.796-0.899) among the mothers who belonged to poorer households, and was lower (OR=0.758, 95% CI=0.717-0.801) among the mothers living in the urban areas. Continuous...